INDUCTION OF FERTILITY THROUGH THE MANAGEMENT OF INCRETIN MIMETIC DRUGS IN PATIENTS WITH POLYCYSTIC OVARY SYNDROME (CIPEEX, 2025)
Introduction: Polycystic ovary syndrome (PCOS) is a multifactorial condition caused by an endocrine-metabolic-ovarian disorder affecting women of reproductive age. This pathology is directly associated with infertility in these patients, and, therefore, both lifestyle modifications and pharmacological treatments are tools to attempt reversal of this condition. Among these, therapy with incretin mimetics and antidiabetic drugs is relevant.Materials and Methods: An integrative literature review was conducted using the PICO strategy: women exposed to hypoglycemic drugs potentially affecting their fertility. The search was performed in PubMed, Scielo, and the BVS indexers – Medline and Lilacs. A total of 45 articles were identified, but only eight met the selected inclusion criteria.Results: Studied incretin mimetics, such as liraglutide and exenatide, were promising in weight reduction as monotherapy; however, when combined with other therapies, results were more significant in terms of weight loss, reduction of serum testosterone levels, and decrease in free androgen concentration. These findings indicated an increase of up to 80% in the pregnancy rate among women with PCOS following the proposed treatments.Conclusion: The findings indicate a relationship between pharmacotherapy with incretin mimetics in PCOS and an increased trend in pregnancy rates among these patients.
Keywords: Fertility; insulin resistance; drug; pharmaco